IMPROVEMENT OF METHODS AND MEANS OF ULTRASONIC CONTROL OF METAL GOODS WITH MODIFIED SURFACE LAYER - A. R. Baev; G. E. Konovalov; A. L. Majorov (Литьë и металлургия, 2011)
In the report perspective methods of diagnostics of surface layers state of products after various technological processes (a face hardening by means of induction or after cementation, coating) are viewed. The testing is carried out to geometrical attributes (thickness of a layer) and presence of flaws. The offered methods of measuring allow making the test in a work cycle of products manufacture.